PEMBENTUKAN SIKAP BERKEBINEKAAN GLOBAL MELALUI TRANSFORMASI PEMBELAJARAN KURIKULUM MERDEKA DI SEKOLAH INDONESIA KUALA LUMPUR - Wijayanti, Inggit; Rahmawati, Asri Nurani (EBTIDA': Jurnal Pendidikan Dasar Islam, 2025)
Education in the era of globalization requires the formation of a global diversity attitude in students to face multicultural challenges. The Merdeka Curriculum, as an innovation in Indonesian education, emphasizes the Pancasila Student Profile Strengthening Project (P5), especially in the dimension of global diversity, which includes cultural awareness, intercultural communication, reflection, and social justice. This study aims to describe and analyze the formation of global diversity attitudes through the transformation of the Merdeka Curriculum at the Indonesian School in Kuala Lumpur (SIKL), one of the Indonesian schools abroad that has implemented this curriculum since the 2022/2023 academic year. The research method used a naturalistic descriptive qualitative approach with data collection techniques of interviews, participant observation, and documentation of four respondents during September – December 2023. Data analysis was conducted using the Miles and Huberman model. The results of the study show that the implementation of the Merdeka Curriculum in SIKL involves P5 project-based learning, discussion, and reflection to foster an attitude of appreciation for the cultural diversity of Indonesia and Malaysia. Various challenges in learning, such as a lack of resources and teacher understanding, can be overcome through quality improvement training and program collaboration. The conclusion of this study is that the transformation of Merdeka Curriculum learning contributes significantly to shaping a global diversity attitude, with recommendations for strengthening environmental support and intensive training for teachers in Indonesian schools abroad. Keywords: Global diversity, Merdeka Curriculum, Pancasila Student Profile, Sekolah Indonesia Kuala Lumpur, Multicultural attitude.